CHARACTERIZATION OF COAL FROM BAYANTEEG DEPOSIT - S, Batbileg; B, Purevsuren; Ya, Davaajav; D, Batkhishig; J, Namkhainorov; M, Battsetseg; J, Narangerel (Proceedings of the Mongolian Academy of Sciences, 2017)
The coal of Bayanteeg deposit was investigated and its technical characteristics, elemental and petrographical maceral compositions were determined. On the basis of proximate, ultimate, petrographic analyses results, it has been confirmed that the Bayanteeg coal is a middle-rank D mark subbituminous coal. The pyrolysis of Bayanteeg coal was studied by using a standard quarts retort (tube) at different heating temperatures and the yields of pyrolysis products such as hard residue, tar, pyrolytic water and gas were determined. The result of these experiments showed that the higher yield 14% of tar can be obtained at heating temperature 500°C. Also the thermal dissolution of Bayanteeg coal was investigated by using a standard stainless steel autoclave at different heating temperatures and the yields of pyrolysis poroducts such as hard residue, tar, pyrolytic water and gas were determined. The tetralin was used as hydrogen donor solvent with constant mass ratio between coal and tetralin (1:1.8). The results of these experiments showed that high yield of tar 48% can be obtained on thermal dissolution of the coal organic mass at 450°C. The solubility of purified pyrolysis tar of Bayanteeg coal in hexane, benzene and dichloromethane was investigated by using silica gel column and the chemical composition of each fraction was determined by using of GC/MS chromatograph system.